THE PARTICIPATION OF THE TURKESTAN MILITARY DISTRICT IN RELATIONS BETWEEN THE RUSSIAN EMPIRE AND AFGHANISTAN (Scientific journal of the Fergana State University, 2023)
This article analyzes the relations between the Russian Empire and Afghanistan in the second half of the 19th-early 20th centuries, the military-political competition of the two countries in Central Asia, its results, the participation of the Turkestan military in this process was analyzed by the administration.